Programa educativo de inteligencia emocional en directivos para mejorar el clima organizacional de las instituciones educativas de nivel inicial distrito San Juan Bautista 2024 - Bardales Manrique, Liliana (2025)
The purpose of this study was to evaluate the effects of implementing an emotional intelligence development program aimed at principals to improve the organizational climate in early childhood educational institutions located within the district of San Juan Bautista during the year 2024. This program used a quantitative quasi-experimental design. The sample included 56 principals, who were divided into an experimental group and a control group. The data collection instrument consisted of an organizational climate questionnaire containing 32 questions. The results showed that the intervention had a highly significant effect on improving the organizational climate (p < 0.01), showing increases in leadership, motivation, effective communication, interpersonal relationships, and decision-making. In conclusion, the implementation of the emotional intelligence program was presented as an effective strategy for transformative change in organizational dynamics, ensuring that the institutional culture fostered a more effective organizational climate in early childhood education, fostering a healthier, more collaborative organizational climate that promoted organizational growth.